Planned birth at or near term for improving health outcomes for pregnant women with gestational diabetes and their infants - Biesty, Linda M (Cochrane Database Syst Rev, 2018)
BACKGROUND: Gestational diabetes is a type of diabetes that occurs during pregnancy. Women with gestational diabetes are more likely to experience adverse health outcomes such as pre‐eclampsia or polyhydramnios (excess amniotic fluid). Their babies are also more likely to have health complications such as macrosomia (birthweight > 4000 g) and being large‐for‐gestational age (birthweight above the 90th percentile for gestational age). Current clinical guidelines support elective birth, at or near term in women with gestational diabetes to minimise perinatal complications, especially those related to macrosomia. This review replaces a review previously published in 2001 that included "diabetic pregnant women", which has now been split into two reviews. This current review focuses on pregnant women with gestational diabetes and a sister review focuses on women with pre‐existing diabetes (Type 1 or Type 2). OBJECTIVES: To assess the effect of planned birth (either by induction of labour or caesarean birth), at or near term (37 to 40 weeks' gestation) compared with an expectant approach for improving health outcomes for women with gestational diabetes and their infants. The primary outcomes relate to maternal and perinatal mortality and morbidity. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth’s Trials Register, ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform (ICTRP) (15 August 2017), and reference lists of retrieved studies. SELECTION CRITERIA: We included randomised trials comparing planned birth, at or near term (37 to 40 weeks' gestation), with an expectant approach, for women with gestational diabetes. Cluster‐randomised and non‐randomised trials (e.g. quasi‐randomised trials using alternate allocation) were also eligible for inclusion but none were identified. DATA COLLECTION AND ANALYSIS: Two of the review authors independently assessed study eligibility, extracted data and assessed the risk of bias of the included study. The quality of the evidence was assessed using the GRADE approach. MAIN RESULTS: The findings of this review are based on a single trial involving 425 women with gestational diabetes. The trial compared induction of labour with expectant management (waiting for the spontaneous onset of labour in the absence of any maternal or fetal issues that may necessitate birth) in pregnant women with gestational diabetes at term. We assessed the overall risk of bias as being low for most domains, apart from performance, detection and attrition bias (for outcome perineum intact), which we assessed as being at high risk. It was an open‐label trial, and women and healthcare professionals were not blinded. There were no clear differences between women randomised to induction of labour and women randomised to expectant management for maternal mortality or serious maternal morbidity (risk ratio (RR) 1.48, 95% confidence interval (CI) 0.25 to 8.76, one trial, 425 women); caesarean section (RR 1.06, 95% CI 0.64 to 1.77, one trial, 425 women); or instrumental vaginal birth (RR 0.81, 95% CI 0.45 to 1.46, one trial, 425 women). For the primary outcome of maternal mortality or serious maternal morbidity, there were no deaths in either group and serious maternal morbidity related to admissions to intensive care unit. The quality of the evidence contributing to these outcomes was assessed as very low, mainly due to the study having high risk of bias for some domains and because of the imprecision of effect estimates. In relation to primary neonatal outcomes, there were no perinatal deaths in either group. The quality of evidence for this outcome was judged as very low, mainly due to high risk of bias and imprecision of effect estimates. There were no clear differences in infant outcomes between women randomised to induction of labour and women randomised to expectant management: shoulder dystocia (RR 2.96, 95% CI 0.31 to 28.21, one trial, 425 infants, very low‐quality evidence); large‐for‐gestational age (RR 0.53, 95% CI 0.28 to 1.02, one trial, 425 infants, low‐quality evidence). There were no clear differences between women randomised to induction of labour and women randomised to expectant management for postpartum haemorrhage (RR 1.17, 95% CI 0.53 to 2.54, one trial, 425 women); admission to intensive care unit (RR 1.48, 95% CI 0.25 to 8.76, one trial, 425 women); and intact perineum (RR 1.02, 95% CI 0.73 to 1.43, one trial, 425 women). No infant experienced a birth trauma, therefore, we could not draw conclusions about the effect of the intervention on the outcomes of brachial plexus injury and bone fracture at birth. Infants of women in the induction‐of‐labour group had higher incidences of neonatal hyperbilirubinaemia (jaundice) when compared to infants of women in the expectant‐management group (RR 2.46, 95% CI 1.11 to 5.46, one trial, 425 women). We found no data on the following prespecified outcomes of this review: postnatal depression, maternal satisfaction, length of postnatal stay (mother), acidaemia, intracranial haemorrhage, hypoxia ischaemic encephalopathy, small‐for‐gestational age, length of postnatal stay (baby) and cost. The authors of this trial acknowledge that it is underpowered for their primary outcome of caesarean section. The authors of the trial and of this review note that the CIs demonstrate a wide range, therefore making it inappropriate to draw definite conclusions. AUTHORS' CONCLUSIONS: There is limited evidence to inform implications for practice. The available data are not of high quality and lack power to detect possible important differences in either benefit or harm. There is an urgent need for high‐quality trials evaluating the effectiveness of planned birth at or near term gestation for women with gestational diabetes compared with an expectant approach.